Gender, depression, and blue-collar work: A retrospective cohort study of U.S. aluminum manufacturers - Elser, Holly (Epidemiology, 2019)
BACKGROUND: Industrial blue-collar workers face multiple work-related stressors, but evidence regarding the burden of mental illness among today’s blue-collar men and women remains limited. METHODS: In this retrospective cohort study, we examined health and employment records for 37,183 blue- and white-collar workers employed by a single U.S. aluminum manufacturer from 2003 – 2013. Using Cox proportional hazards regression, we modeled time to first episode of treated depression by gender and occupational class. Among cases, we modeled rates of depression-related service utilization with generalized gamma regression. RESULTS: Compared with their white-collar counterparts, blue-collar men were more likely to be treated for depression (HR = 1.3, 95% CI 1.1 – 1.4) as were blue-collar women (HR = 1.4, 1.2 – 1.6). Blue-collar women were most likely to be treated for depression as compared with white-collar men (HR = 3.2, 95% CI 2.1 – 5.0). However, blue-collar workers used depression-related services less frequently than their white-collar counterparts among both men (RR = 0.91, 95% CI 0.84 – 0.98) and women (RR = 0.82, 95% CI 0.77 – 0.88). CONCLUSION: Blue-collar women were most likely to be treated for depression compared with white-collar workers, and blue-collar women were most likely to be treated for depression compared with white-collar men. However, blue-collar men and women used depression-related healthcare services less frequently than white-collar workers. These findings underscore that blue-collar women may be uniquely susceptible to depression, and suggest that blue-collar workers may encounter barriers to care-seeking related mental illness other than their insurance status.